GAYA KEPEMIMPINAN DIREKTUR TERHADAP FUNGSI KEPEMIMPINAN DIREKTUR DALAM MELAKSANAKAN MANAJEMEN DI RUMAH SAKIT PELAMONIA MAKASSAR - Guntur Suryo Putro (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this study was to determine the effect of Leadership Style Director Of Function Leadership Director of Undertaking Management In Hospital Pelamonia Makassar, the results of research that has been done, it is obtained that There is a significant relationship between leadership style and flexibility of leadership style to function leadership but there is no significant correlation between the effectiveness of leadership style with leadership functions. The individual characteristics by long working director to director assessed and the type of training that followed had a significant relationship to the function of leadership, while gender and type of education directors did not have a significant relationship to the function of leadership. Results OR of long work became director assessed the function of leadership to come by 0.144 means that directors who have long work became director who rated less than 1 year likely to be assessed as having a leadership function "good" by 0.144 times greater than the director with a long working directors rated greater than or equal to 1 year. It is possible in the director with a long work became director who rated less than 1 year have managerial experience hospital longer than the director who has long work became director who rated more than 1 year and length of employment effect on the onset of saturation resulting in dilution of innovation especially development the new program also from the staff has been more deeply familiar with the director connected the downside.